Kinerja Keuangan Perbankan Syariah: Tinjauan Dari Intellectual Capital Pada BNI Syariah - Hastuti Olivia; Gadis Arniyati Athar; Tia Andrianti Nasution; Syahrijal Hidayat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study aims to analyze the effect of intellectual capital (IC) on financial performance at Bank Negara Indonesia (BNI) Syariah. The hypothesis in this study was tested using the variant-based Structural Equation Modeling (SEM) method or Partial Least Square (PLS) involving several variables of intellectual capital (IC) modified for Islamic banking such as iB-VACA, iB-VAHU, iB-STVA. The results showed that iB-VAIC and iB-VACA) had an effect on financial performance. Meanwhile, iB-VAHU has no effect on financial performance, and iB-STVA has a negative effect on financial performance